AWQAF AND ITS IMPORTANCE IN A MODERN ECONOMIC SYSTEM (Journal of Economic Research & Business Administration, 2019)
The paper traced the essential functions and role of awqaf that it played in the past and still providing socio-economic services for the society. The paper provides explicitly the experiences of a few organizations, which play a significant role in this direction and made some recommendations for the improvement of the sector in the present circumstances. Islamic history is full of instances that the individuals and the ruling classes have donated their valuables for the religious, social and other public goods as well. Waqf institutions are working for the welfare of the community through the provision of education, health, training, and capacity building, providing finance and opportunity of employment, food and other basic needs, and help and support in natural disasters. However, these services can be provided at a larger scale as well, which depends mainly on the size of the waqf and flow of resources. Although governments are providing essential services to their societies, however, available resources bind their hand tight, and always there is a need for additional resources to serve the left out people. Waqf is a third sector, which can be utilized for the additional resources for the provision of basic needs and safety nets for the poor. Studies have shown that if saqaqat and waqf have been explored and appropriately utilized, then enough resources can be made available for poverty eradication. The tragedy is that the outcome of the present awqaf is not enough to even manage the mosques properly. However, for revitalizing and effectively utilizing waqf resources, serious efforts are needed. Governments may provide the proper environment and legal framework for the creation, investment and development of waqf. It may recover lost waqf and give space to the civil society and private sector by incentivizing them for the establishment of waqf.